80. Heme Oxygenase-1 Gene promoter and associations with inflammation and subclinical vascular disease in Ugandan adolescents with and without HIV. (4th December 2021) - Dirajlal-Fargo, Sahera; Sattar, Abdus; Musiime, Victor; Kityo, Cissy; Robbins, Reuben N; Santoro, Anthony F; Ferraris, Christopher; Garcia-Mesa, Yoelvis; McComsey, Grace A; Kolson, Dennis
Abstract: Background: Heme oxygenase-1 (HO-1) is a cytoprotective enzyme with potent anti-inflammatory, and anti-oxidant effects. The HO-1 response is modulated by functional polymorphisms (a dinucleotide (GT)n repeat length variation) in the HO-1 gene promoter region which have been associated with cardiovascular disease (CVD) susceptibility in adults. HO-1 polymorphisms and their associations with markers of inflammation and CVD in Ugandan adolescents with (HIV+) and without HIV (HIV-) have not been investigated. Methods: We included 177 children (92 HIV+, 85 HIV-) enrolled in an ongoing observational cohort study at the Joint Clinical Research Center, Kampala, Uganda. All HIV+ participants were on ART. HO-1 (GT)n allele genotypes were determined by PCR of the (GT)n repeat region followed by fragment size determination on a capillary sequencer in DNA extracted from blood samples. Allele designations were assigned by number of (GT)n repeats: S < 27, M 27-34, or L > 34 repeats. We measured mean common carotid artery intima-media thickness (IMT) as a marker of CVD, markers of systemic inflammation (hsCRP, IL6, sTNFRI), monocyte activation (sCD14 and sCD163), and T-cell activation (expression of CD38 and HLA-DR on CD4+ and CD8+), oxidized lipids, markers of gut integrity and fungal translocation (BDG). Results: Median age (IQR) was 13 (11, 14), 44% were females, 86% had viral load < 20 copies/mL. 19% had a short allele genotype, 37% had a medium allele genotype and 44% had a long allele genotype (Figure). The shortest and longest allele length correlated with lower IMT in HIV- only (r=-0.36 and -0.30, respectively, p≤ 0.01 for both). Among biomarkers, only the medium allele correlated with oxidized lipids in HIV+ and with hsCRP and BDG in HIV- (p≤ 0.05). After adjusting for age, sex, and BMI, the presence of a long allele was associated with lower IMT. This was no longer significant after adjusting for markers of inflammation or oxidized lipids (Table). Heme Oxygenase-1 genotype allele length frequency in Ugandan cohort of HIV+ and HIV- youth 1: Models are adjusted for age (years), sex (male vs female), BMI (kg/m2) and HIV status (positive vs negative) 2: Models are adjusted for age (years), sex (male vs female), BMI (kg/m2), sCD14 (pg/mL) and HIV status (positive vs negative) 3: Models are adjusted for age (years), sex (male vs female), BMI (kg/m2), high sensitivity C reactive protein (ng/mL) and HIV status (positive vs negative) 4: Models are adjusted for age (years), sex (male vs female), BMI (kg/m2), oxidized lipids and HIV status (positive vs negative) Conclusion: These findings underscore the potential of the HO pathways in modulating future risk for CVD in adolescents through inflammation. HIV status in this setting, likely influences the associations with the genotype with the risk of CVD. Further studies to validate our findings in this population are required. Disclosures: Grace A. McComsey, MD, Gilead (Consultant, Advisor or Review Panel member)Janssen (Consultant, Advisor or Review Panel member)Merck (Consultant, Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)Redhill (Research Grant or Support)Roche (Grant/Research Support)Tetraphase, Astellas (Research Grant or Support)Theratechnologies (Consultant)Vanda (Grant/Research Support)ViiV/GSK (Scientific Research Study Investigator, Advisor or Review Panel member)